Perdão: uma busca interior - Garcia, Ariane Tescaro (2010)
This study aims to understand, based on Analytical Psychology, the role of forgiveness in the psyche. Because of forgiveness be extremely tied to religion, it is fundamental to understand it, primarily, within the religious context, then, explore how it was experienced in psychic terms. With the aid of Symbolic Jungian Psychology, it is possible understand how the development of Judeo-Christian religion was understood and lived symbolically in our society and how patterns of consciousness prevailing influence not only the experience of forgiveness, but also its opposite pole, revenge. From this foundation, a sense of forgiveness was sought in the process of individuation, raising the chances that it can paralyze the process, when living in a superficial way, or make it easier, when experienced in a genuine way. Another aspect discussed was the importance of forgiveness in the analytical process. Finally, in order to illustrate the theoretical work here developed, the film Invictus, by director Clint Eastwood, was analyzed, since it discusses the polarity revenge-forgiveness in both personal and cultural aspects